Uno sguardo sulla scuola Il Seminario "I dati INVALSI: uno strumento per la ricerca" - Falzetti, Patrizia (INVALSI per la ricerca - Open Access, 2019)
The second edition of the Seminar "INVALSI data: a tool for research" was held in Florence on 17 and 18 November 2017. The event was an opportunity to meeting and networking among researchers, teachers, school managers and, more generally, all those who have an interest in educational evaluation and the data made available by INVALSI every year. The INVALSI data, in fact, although not claiming to be exhaustive about the complexity of the school world, are useful to understand some educational phenomena more effectively. The INVALSI Statistical Service has decided to collect the numerous research contributions presented on this occasion in specific thematic sessions. This volume contains 13 chapters which, starting from different points of view and using heterogeneous methodological approaches, provide insights into how INVALSI data can contribute to deepening the interpretation of the school world, in its different aspects. The reading path is rich and complex and can serve as a landmark for those wishing to explore some issues concerning the Italian system.